Corrosion study on X70-carbon steel material influenced by soil engineering properties - Lim, Kar Sing (2012)
Corrosion of metals in soil can vary from relatively rapid material loss to negligible effects, depending on soil environment. Soil engineering properties and soil contents are important parameters that may influence soil corrosivity and level of corrosion dynamic. Previous researches had investigated the soil corrosiveness, but mainly focused on the soil chemical content instead of soil engineering properties. Hence, this research aims to investigate the relationship of soil engineering properties towards corrosion dynamic (metal weight loss and corrosion growth pattern) of grade X70 carbon steel material and to classify the soil properties according to power law constants, k and v. The study focuses on four types of major soil engineering properties which are moisture content, clay content, plasticity index and particle size. Actual field work, simulated field work and laboratory test have been carried out to measure the metal weight loss influenced by soil properties. Five sites located in the east coast of Peninsular Malaysia (Terengganu, Pahang and Johor) were identified for actual field work and seven types of soil were collected and brought to the Universiti Teknologi Malaysia (UTM) site in Johor Bahru for simulated field work. Laboratory work was carried out by exposing the steel coupons to different intensities of soil properties under controlled environment. Graphical and statistical analyses were carried out to study the relationship between soil engineering properties and corrosion dynamic. The analyses consist of simple scatter plot, identification of outliers, normality test, simple linear regression analysis (SLR), correlation analysis, principal component analysis (PCA), paired t-test and multiple regression analysis. Moisture content recorded the highest R2 of 0.369 from single regression analysis. The significant p-value of moisture content, 0.041 from multiple linear regression is the only p-value that satisfied the limit of significant pvalue of 0.05, indicates its superior dominance upon metal weight loss. PCA has classified moisture content into Component-1 of metal loss constant, k while plasticity index and particle size are grouped into similar component of corrosion growth pattern constant, v. Similar findings were also observed through t-test. As a conclusion, the research has indicated moisture content as the most governing factor on metal loss constant, k while plasticity index, particle size and clay content have strong to modest influence on corrosion growth pattern constant, v. The findings have revealed the importance of soil engineering properties upon the mechanism of corrosion modelling especially when power law principal is adopted to predict the future metal weight loss.